Criatividade em educação escolar: estudo de caso - Mendes, Laudicelia Gomes Pessoa (1984)
This work consists a study about creative methodology in schools. Having bc1sed studies concluded by G.lilford, Torrence and Kneller, a practical investigation was sUrlied, which took place in a private college in são Luís(MA). The college enhances students capacities and developrnent. The objectivity of this task was to verify the importance in how teachers attribute the activities which make creativeness possible and thus having an analysis. Through the rreth:dology adopted by the teachers, if the factors in question 'simpl! fy' or help creativeness, according tokneller are being developed in the classroom, and it is from this point tbat rew work and research is stirred up. A number of teachers were interviewed from the primary schools, (19 grau - 8a. serie) and high schools, (29 grau-la.-2a. series) besides observing their endurance in the classroom. The facts gathered were analysed according to Guilford and Kneller's facilitation of creativeness. The results were compared with the college's proposal. However, we must be aware that the teachers under study have theoretical knowledge about the necessity of making the act of teaching much more interesting a~ d~c, through activities considered by them to be suitable for developing creativeness. In practice, however, we can ob~e that the lessons in general were exhibited, with a predominance of unilateral information of the teachers who seemed to be determined only in transmiting the contents of discipline and not creating an opportunity for the development of creativeness of the students. Verifying this there was reason to believe that ~ teachers found difficulties accompli~hing their practice at pedagogy aimed at the process of creative learning. Among other diff icul ties, we can also inc lude the n\.lI':ll::)t;y of students in a class, the utili ty of books that contain D::lsic exercises for memorising and students on the whole don't accept the fact of adopting the books that the college uses. With an analyses of the results of the application of instrurnents, there has arisen a hipothesis that they are having problems in the relation between teacher and student, chiefly caused by the action of the correct way of teaching, which has not been accomplished by some of the teachers. However, the major objectivity of the school was to promote a creative education which is also dynamic, and fin ding ways of developing an attitude which is creative and reflexive, but this is not taking place. In conclusion, besides having creativeness tMt favourssurroundings, the school needs teachers who allow free manifestation of creative potencial of the students, and for this to happen, it would be necessary for the teacher to accept and merit the creative individual.